Influence of crown-to-implant ratio on periimplant marginal bone loss in the posterior region: a five-year retrospective study - Lee, Kyung-Jin (Korean Academy of Periodontology, 2012)
PURPOSE: The aim of this study was to evaluate the influence of the crown-to-implant (C/I) ratio on the change in marginal bone level around the implant and to determine the site-related factors influencing the relationship between the C/I ratio and periimplant marginal bone loss. METHODS: A total of 259 implants from 175 patients were evaluated at a mean follow-up of five years. Implants were divided into two groups according to their C/I ratios: ≤1, and >1. Site-related factors having an influence on the relationship between C/I ratio and periimplant marginal bone loss were analyzed according to the implant location, implant diameter, implant manufacturer, prosthesis type, and guided bone regeneration (GBR) procedure. RESULTS: It was found that 1) implants with a C/I ratio below 1 exhibited greater periimplant marginal bone loss than implants with a C/I ratio more than 1, 2) site-related factors had an effect on periimplant marginal bone loss, except for the implant system used, 3) the C/I ratio was the factor having more dominant influence on periimplant marginal bone loss, compared with implant diameter, prosthesis type, implant location, and GBR procedure, 4) implants with a C/I ratio below 1 showed greater periimplant marginal bone loss than implants with a C/I ratio greater than 1 in the maxilla, but not in the mandible, 5) and periimplant marginal bone loss was more affected by the implant system than the C/I ratio. CONCLUSIONS: Within the limitations of this study, implants with a higher C/I ratio exhibited less marginal bone loss than implants with a lower C/I ratio in the posterior regions. The C/I ratio was a more dominant factor affecting periimplant marginal bone loss in the maxilla than the mandible. Meanwhile, the implant system was a more dominant factor influencing periimplant marginal bone loss than the C/I ratio.